Parametric investigation of a non-constant cross sectional area air to air heat exchanger - Cárdenas, Bruno; Garvey, Seamus; Kantharaj, Bharath; Simpson, Michael (Elsevier, 2017)
The present article addresses the design, mathematical modelling and analysis of a novel highly exergy-efficient air to air heat exchanger. An intricate design based on an hexagonal mesh is proposed for the cross-sectional area of the heat exchanger with aims to explore the performance gains that can be obtained by exploiting the capabilities and benefits offered by modern fabrication techniques such as additive manufacturing. Special attention is paid to understanding the relationship or trade-off that exists between the overall exergy efficiency of the heat exchanger and its cost.